The Thai anesthesia incident monitoring study (Thai AIMS) of postoperative central neurological complications - Patiparn Toomtong (2018)
Objective: To analyze the incidents of central neurological complication in the Thai Anesthesia Incident Monitoring Study (Thai AIMS). Material and Method: A prospective descriptive multi-centered study of incident reports was conducted in 51 hospitals across Thailand from January to June 2007. Voluntary and anonymous reports of any adverse events during the first 24 hrs of anesthesia were sent to the Thai AIMS data management unit. Three anesthesiologists reviewed the possible central neurological complication reports. Descriptive statistics was used. Results: There were 16 relevant incident reports of central neurological complications (7 cases of convulsion, 5 cases of cerebro-vascular accident and 4 cases of coma). Majority of patients appeared to be old with underlying co-morbidities undergoing major surgical procedures under general anesthesia and required more intensive intra-operative monitoring. These complications occurred commonly with patients of orthopedics, cardiac, urologic and neurosurgical surgery. The majority of cerebro-vascular accident (80%) and coma (75%) were considered preventable. Conclusion: Inappropriate decision making and inexperienced anesthesiologists were common contributing factors while suggested corrective strategies were quality assurance activity, clinical practice guidelines and improvement of supervision.